Evolutionarily Conserved Repulsive Guidance Role of Slit in the Silkworm Bombyx mori - Yu, Qi (Public Library of Science, 2014)

(untitled)
Axon guidance molecule Slit is critical for the axon repulsion in neural tissues, which is evolutionarily conserved from planarians to humans. However, the function of Slit in the silkworm Bombyx mori was unknown. Here we showed that the structure of Bombyx mori Slit (BmSlit) was different from that in most other species in its C-terminal sequence. BmSlit was localized in the midline glial cell, the neuropil, the tendon cell, the muscle and the silk gland and colocalized with BmRobo1 in the neuropil, the muscle and the silk gland. Knock-down of Bmslit by RNA interference (RNAi) resulted in abnormal development of axons and muscles. Our results suggest that BmSlit has a repulsive role in axon guidance and muscle migration. Moreover, the localization of BmSlit in the silk gland argues for its important function in the development of the silk gland.